The Cavitation Characteristics of High Speed Centrifugal Pumps With Different Impeller Types - Chao, Wen-xiong; Shi, Bao-lu; Ruan, Hui; Dong, Wei (Frontiers in Energy Research, 2022)
Addressing the cavitation prevention requirements for a longer service life of the high-speed centrifugal pump in the temperature control system of aerospace, the effect of blade inlet width on cavitation performance is studied on the premise of consistency of impeller outlet diameter D2, impeller outlet width b2, volute inlet diameter D3, pump interface and other structural parameters. Therefore, the corrected coefficient k1 of blade inlet exclusion coefficient is introduced; four groups of centrifugal impellers with inlets of different geometric structures blades are put forward. To begin with, based on the D# pump performance test and Pumplinx simulation, the cavitation performance of high-speed pump with four different groups of impellers is studied under five working conditions of negative inlet pressure (Pj=(−20, −30, −40, −50, −60)kPa) on the premise that energy characteristics agree well with cavitation performance. According to the results, when Pj drops from −50 kPa to −60 kPa, the cavitation perform changes the most significantly. This indicates that the method of twisting the centrifugal impeller of the suspended forward-extended blade shows a significant effect in preventing cavitation performance under such working conditions of high speed and negative pressure. Its application in aerospace power systems can effectively reduce the impact of low pressure in the system and significantly improve the cavitation performance.